Architects of Structural Biology: Bragg, Perutz, Kendrew, Hodgkin. By John Meurig Thomas. Oxford University Press, 2020. Pp. 320. GBP 35 (hardback), ISBN 9780198854500. Issue 1 (6th January 2021) - Liljas, Anders
Abstract : A book on the history of four pioneers in structural biology, written by the late John Meurig Thomas, is reviewed. Abstract : A book on the history of four pioneers in structural biology, written by the late John Meurig Thomas, is reviewed.